The Existence Principle Assertion in Authority Supervision Finance By Examining Body Finance in Indonesia - SIKUMBANG, Yudhia Perdana; SARAGIH, Geofani Milthree (Indonesia Strategic Sustainability, 2024)
Examining Body Finance is state agency that has authority inspection finance in Indonesian constitution , p the by constitutional set in _ Article 23E paragraph (1) of the 1945 Constitution. In operate function inspection state finances , the BPK in run it bound by principle assertion . However in level implementation , still there is action examinations carried out by the BPK in Thing this no notice principle assertion . Study this will study existence principle assertion in implementation authority inspection state finances by the BPK. Study this categorized as to in type study normative with based on problem or raised theme _ as topics study main inside _ study this . Approach used _ in study this is approach principle law with link a number of law existing positive _ During regarding with topics discussion main inside _ study this . Method analysis used _ is descriptive analytical with describe regulation current legislation _ apply as well as decisions later court _ linked with practice the law that occurs in the field ( facts ) law ). Research results this show that existence than principle assertion in law positive , practice law until guide for CPC in operate authority inspection to real state finances has emphasized even inside _ law related positive _ with CPC no someone confirmed _ by textual about role as well as attachment from principle assertion .